Modeling the Impact of Foreign Direct Investment on China’s Carbon Emissions: An Economic and Environmental Paradigm - Xiao, Yuanzhi; Gao, Ke; Sun, Ruiqi (Frontiers in Environmental Science, 2022)
Under the background of high-quality development, the impact of foreign direct investment on carbon emissions has attracted increasing attention. This research studies the impact of foreign direct investment on carbon emissions under the effect of institutional quality regulation. Specifically, this study uses China’s provincial panel data from 2010 to 2019, taking political system quality, economic system quality, and legal system quality as the external environment of system quality, this research studies the threshold effect of foreign direct investment on carbon emissions. The results show that foreign direct investment can effectively restrain the increase in carbon emissions. The impact of FDI on China’s carbon emissions has an obvious economic threshold effect: with the increase of regional corruption, the political quality is gradually declining, and the inhibition effect of foreign direct investment on carbon emissions is declining. With the increase of marketization and intellectual property protection, the regional economic system and legal system have gradually improved, and the role of foreign direct investment in carbon emissions has been further increased. Therefore, China should create a good institutional environment for FDI technology spillovers.